2010
DOI: 10.1097/smj.0b013e3181e633aa
|View full text |Cite
|
Sign up to set email alerts
|

Myositis as an Unusual Presentation of Secondary Syphilis

Abstract: Myositis is a complication of many infectious and noninfectious processes. Secondary syphilis is an uncommon cause of myositis, and, therefore, the diagnosis may be delayed. We describe a man with human immunodeficiency virus infection presenting with diffuse muscle injury secondary to syphilis. He had complete resolution of all signs and symptoms after treatment with intravenous penicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…3 Rhabdomyolysis and acute kidney injury: while myalgia is common in both primary and secondary stages of syphilis, inflammatory myopathy causing severe acute kidney injury is rare. 26 It is more common in association with HIV infection; hence, a presentation with myositis and rhabdomyolysis in a patient with syphilis 26,[37][38][39] should prompt testing for HIV. 4 Syphilitic aortitis with renal infarct: in the tertiary stages of syphilis, the Treponema pallidum can invade the aortic wall and incite a vasculitic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Rhabdomyolysis and acute kidney injury: while myalgia is common in both primary and secondary stages of syphilis, inflammatory myopathy causing severe acute kidney injury is rare. 26 It is more common in association with HIV infection; hence, a presentation with myositis and rhabdomyolysis in a patient with syphilis 26,[37][38][39] should prompt testing for HIV. 4 Syphilitic aortitis with renal infarct: in the tertiary stages of syphilis, the Treponema pallidum can invade the aortic wall and incite a vasculitic response.…”
Section: Discussionmentioning
confidence: 99%
“…In all these case reports, treatment with penicillin lead to complete resolution of the nephrotic or nephritic syndrome and skin lesions when present. Rhabdomyolysis and acute kidney injury: while myalgia is common in both primary and secondary stages of syphilis, inflammatory myopathy causing severe acute kidney injury is rare 26 . It is more common in association with HIV infection; hence, a presentation with myositis and rhabdomyolysis in a patient with syphilis 26,37–39 should prompt testing for HIV. Syphilitic aortitis with renal infarct: in the tertiary stages of syphilis, the Treponema pallidum can invade the aortic wall and incite a vasculitic response. This weakens the tunica to form aneurysms and associated aortic valvular insufficiency 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been occasional reports of some diseases that are related to syphilis infection, such as ophthalmia, orchitis, myositis, sudden deafness, and multiple intracranial aneurysms . However, since the 1940s, discussion about the association of syphilis with DM has been rare, let alone the relationship between NS and DM.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been occasional reports of some diseases that are related to syphilis infection, such as ophthalmia, orchitis, myositis, sudden deafness, and multiple intracranial aneurysms. [14][15][16][17][18] However, since the 1940s, discussion about the association of syphilis with DM has been rare, let alone the relationship between NS and DM. Half a century ago, there were two main opinions on the relationship between syphilis and DM: a few studies reported that syphilis could directly or indirectly induce DM, 19,20 whereas others did not think there was any association between the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus anginosus infection of muscle is likely even less common [73]. In some rare cases, muscle infection by Treponema pallidum has been reported and some patients had secondary syphilis after HIV infection [74,75]. Because fungal infection is closely related to the immune status of patients, fungal myositis is found mainly in immunocompromised patients after HIV infection or organ transplantation and Aspergillus is a common cause in these cases [76][77][78].…”
Section: Recent Findings On Infectious Myopathymentioning
confidence: 99%